Stability of two-inertia system using non-linear controller: application to drive-control system of electric vehicle - Mubin, M.; Ouchi, S.; Kodani, N.; Mokhtar, N.; Soin, N. (2008)
The drive-control system of a vehicle is considered as two-inertia system that is the wheel system and the carbody system. This paper firstly presents the stabilization of two-inertia system using a non-linear controller and a disturbance observer. This control system is then applied to a drive-control system of a vehicle with a disturbance observer for estimating the car-body speed. A Lyapunov stability theorem is followed to confirm the stability of the system. The effectiveness of this control system is proved by a satisfactory experimental results. Â©ISAROB 2008.